Practical Implementation of SCADA System for Falluja Substation - Mohammed Salih, Salih (Anbar Journal of Engineering Sciences, 2009)
The Digital control systems for substations have been installed in different areas of Iraq in the recent years. Most of these techniques used a Supervisory Control And Data Acquisition (SCADA) with Remote Terminal Unit (RTU) for monitoring the metering devices for incoming and outgoing feeders, while the other system used a Programmable Logic Control (PLC) technique for controlling and monitoring the system inside substations by professional engineers. A practical monitoring system of SCADA with RTU has been introduced in this paper for Falluja substation. There are 3 devices of RTUs are used to collect data from ION 6200 devices installed inside incoming and outgoing panels for low Voltage (LV 380V), 33KV and 11KV, then the data from each RTU will be send to the SCADA (main Computer) via special router, the SCADA system used ION enterprise software supplied by AREVA company in addition to all panels which supplied by the same company. Many difficulties were appeared during the work, such as mistakes of IPs, setting parameters, selection of protocols, and matching of devices have solved until the normal work was obtained to the substation.